Nondestructive estimation of pomegranate tree biomass by using allometric equation: Nondestructive Estimation of Pomegranate Plant Biomass - Arkalgud, Ganeshamurthy Nanjundaiah; T.R, Rupa; Karasula, Alivelu (Annals of Arid Zone, 2023)
The current method available for nondestructive estimation of tree biomass using diameter at breast height (DBH) or other parameters is not applicable to pomegranate bushes, which have multiple stems emerging from the ground level. Therefore, pomegranate bushes in commercial orchards require an independent allometric equation for the nondestructive estimation of plant biomass. Using destructive sampling and parameters other than DBH, a pomegranate-specific allometric equation was developed. The selected allometric parameters were significantly related to the age of the trees. The root-to-shoot ratio (0.231) was also different from the 0.26 reported for forest trees. The biomass expansion factor (BEF) has by and large attained stability beyond 8 years of orchard age. The developed equations generally fit the data well, and in most cases, the product stem girth (SG) x number of stems (NS) explained more than half of the observed variation in biomass. Though there was a good agreement between the observed and predicted biomass using both multiple linear regression (MLR) and the power model, the MLR overestimated the biomass. Hence, based on R2 values and the estimated biomass, it is suggested to use the power model to predict the pomegranate bush biomass.